Odpowiedzi

2010-02-04T18:29:38+01:00

(2x + 3)² = 4x²+18x+9

(3y + 1)² = 9y²+6y+1

(1/2 xy + 2)² = 1/4x²y²+2xy+4

(3 + x)² = 9+6x+x²

(-2x - 3)² = 4x²+12x+9

(-6xyz + 1)² = 36x²y²z²-12xyz+1

(-4xy-2)² = 16x²y²+16xy+4

( 1/5a + 1)² = 2.25a²+3a+1
nie wiem czy przed otatnie jest dobrze

2010-02-04T18:30:58+01:00
A) (2x + 3)² = 4x²+18x+9

b) (3y + 1)² = 9y²+6y+1

c)(1/2 xy + 2)² = 1/4x²y²+2xy+4

d) (3 + x)² = 9+6x+x²

e)(-2x - 3)² = 4x²+12x+9

f) (-6xyz + 1)² = 36x²y²z²-12xyz+1

g) (-4xy-2)² = 16x²y²+16xy+4

h) ( 1/5a + 1)² = 2.25a²+3a+1
2010-02-04T18:31:49+01:00
A) 2x²+9
b) 3y²+1
c) ¼x²y²+4
d) 9+x²
e) 4x²+9
f) 36x²y²z²+1
g) 16x²y²+4
h) 1/25a²+1